SmartPads - Encouraging Children's Physical Activity Using a Multimedia Edutainment System - Hafidh, Basim (Université d'Ottawa / University of Ottawa, 2012)
This thesis presents an exercise-based edutainment system intended for children. It is designed to enhance their cognitive development by encouraging movement in a fun way. The main idea behind the system is that children will have fun constructing a physical, tangible user interface. In addition, they will learn how to spell many words that represent objects and entities by stepping on a collection of coloured pads and receiving responses through a set of multimedia outputs related to these entities. For this purpose we have designed and implemented a tangible user interface that facilitates interaction with the system. This tangible user interface is called "SmartPads" and is composed of coloured tiles that can be physically connected to each other to form any shape. The pads are mapped onto a computer screen in real-time. A user interacts with the interface by stepping on the pads. We have incorporated two games that allow children of different ages to benefit from the system's functionalities and encourage them to interact with it. This thesis provides detailed information about the proposed system and its related components, discusses the design and development of the two games, and measures the system's performance when used by the children.
Keywords: Multimedia; Edutainment; Exergaming; Tangible user interface